Genetic and Environmental Influences on the Affective Regulation Network: A Prospective Experience Sampling Analysis - Hasmi, Laila; Drukker, Marjan; Guloksuz, Sinan; Viechtbauer, Wolfgang; Thiery, Evert; Derom, Catherine; van Os, Jim (Frontiers in Psychiatry, 2018)
Background: The study of networks of affective mental states that play a role in psychopathology may help model the influence of genetic and environmental risks. The aim of the present paper was to examine networks of affective mental states (AMS: ‘cheerful’, ‘insecure’, ‘relaxed’, ‘anxious’, ‘irritated’ and ‘down’) over time, stratified by genetic liability for psychopathology and exposure to environmental risk, using momentary assessment technology. Methods: Momentary AMS, collected using the experience sampling method (ESM) as well as childhood trauma and genetic liability (based on the level of shared genes and psychopathology in the co-twin) were collected in a population-based sample of female-female twin pairs and sisters (585 individuals). Networks were generated using multilevel time-lagged regression analysis, and regression coefficients were compared across three strata of childhood trauma severity and three strata of genetic liability using permutation testing. Regression coefficients were presented as network connections. Results: Visual inspection of network graphs revealed some suggestive changes in the networks with more exposure to either childhood trauma or genetic liability (i.e. stronger reinforcing loops between the three negative AMS anxious, insecure, and down both under higher early environmental, and under higher genetic liability exposure, stronger negative association between AMS of different valences: i.e. between ‘anxious’ at t-1 and ‘relaxed’ at t, ‘relaxed’ at t-1 and ‘down’ at t, under intermediate genetic liability exposure when compared to both networks under low and high genetic liability). Yet, statistical evaluation of differences across exposure strata was inconclusive. Conclusions: Although suggestive of a difference in the emotional dynamic, there was no conclusive evidence that genetic and environmental factors may impact ESM network models of individual AMS.